Families’ involvement at schools: the perspective of the psychosocial duos - Gandarillas, Andrea Precht; Anabalón, Yasna Anabalón (International Journal of Evaluation and Research in Education (IJERE), 2025)
This article aims to investigate the perspective on family involvement of social workers and school psychologists. Based on a qualitative study, we analyzed a corpus of four interviews with psychosocial duos from state-subsidized public schools. We analyzed these interviews by conducting a thematic analysis. The results show that for these professionals, family involvement would ensure the educability of students in a framework of individual parental responsibility, understanding the efforts of schools as a support to the work of parents and guardians. The consequences and relationships of these perspectives for the work with school communities in the framework of public education are discussed.